Using gamification to support learning English as a second language: a systematic review. Issue 7 (3rd September 2021) - Dehghanzadeh, Hojjat; Fardanesh, Hashem; Hatami, Javad; Talaee, Ebrahim; Noroozi, Omid
Abstract: Digital gamification has been argued to be a fun and enjoyable method to support Learning English as a Second Language (LESL) and to ease the gap between students' learning and educational practice. This systematic review presents an overview of the state of the art on the use of gamification for LESL in digital environments. Furthermore, this review study maps learning experiences of learners and their learning outcomes when they deal with LESL through gamification. For this systematic review, 22 publications dating from 2008 through 2019 were studied to highlight the foci of this field of research. Although, these studies reported positive effects of gamification on learners' learning experiences and their learning outcomes, none of the publications reported specific gamification elements associated to the learning experiences and outcomes. Being enjoyable, engaging, motivating and fun were positive learning experiences of gamified LESL environments. Content language learning, engagement, motivation, and satisfaction were targeted learning outcomes of gamified LESL. The results of this study provide suggestions on how to design digital gamification for students' LESL and their corresponding learning experiences and outcomes.